1981
DOI: 10.5006/1.3593848
|View full text |Cite
|
Sign up to set email alerts
|

An Initial Investigation of Calcareous Deposits upon Cathodic Steel Surfaces in Sea Water

Abstract: The influence of potential and nominal sea water velocity upon the nature of calcareous deposits formed upon a cathodic steel surface has been investigated. Specific attention was focused upon change with exposure time of the current density to maintain a prescribed cathodic potential and upon thickness of the calcareous film. Equations have been developed whereby pH of the electrolyte adjacent to both a filmed and film-free surface can be rationalized in terms of cathodic current density and character of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 0 publications
3
42
0
Order By: Relevance
“…After the initial 100 h less than 25% of the current required to polarize the steel in 3.5% w/v NaCl was required to polarize in the synthetic seawater due to the deposition of the calcareous coating. The current density decay over the experiment for this coating is comparable with previous findings for a mixed Mg(OH)2 and CaCO3 deposit [9,33]. Figure 6a,b show pH measurements for the two solutions 3.5% w/v NaCl and synthetic seawater.…”
Section: Visual Observationssupporting
confidence: 76%
See 1 more Smart Citation
“…After the initial 100 h less than 25% of the current required to polarize the steel in 3.5% w/v NaCl was required to polarize in the synthetic seawater due to the deposition of the calcareous coating. The current density decay over the experiment for this coating is comparable with previous findings for a mixed Mg(OH)2 and CaCO3 deposit [9,33]. Figure 6a,b show pH measurements for the two solutions 3.5% w/v NaCl and synthetic seawater.…”
Section: Visual Observationssupporting
confidence: 76%
“…Calculations for the pH required for the deposition have yielded values of pH 7.3-8.7 for the CaCO3 polymorphs (calcite and aragonite) and pH 9.3-11.25 for brucite (Mg(OH)2 [6,7,[9][10][11] and the composition achieved dependent on the potential applied, temperature, and flow of the electrolyte (ASTM D1141 [12] in our case) [9,[13][14][15]. In previous studies it has been established that the deposit has a two layer structure made up of a fine layer of Mg-rich brucite followed by a Ca-rich polymorph [7,14,[16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the presence and formation of a thin inner layer of magnesium hydroxide on the steel, under cathodic protection, is attributed to a high level of alkalisation (above 10) near the surface due to the reduction of oxygen and at very low potentials, due to the process of water reduction [2,5,6,15]. This statement is very well justified for cathodically protected steel, which has no evidence of corrosion.…”
Section: Examination Of Calcareous Deposits By Sem With Edxmentioning
confidence: 84%
“…When steel is under cathodic protection in seawater, the pH near the steel surface slowly becomes more alkaline due to oxygen reduction [2] and the deposition of calcium carbonate is expected to occur first. In previous studies [3,5,6,17] it was demonstrated that the compound that is initially precipitated next to the iron-containing corrosion products is possibly brucite (Mg(OH)2), and not calcium-rich aragonite (calcium carbonate, CaCO3).…”
Section: Theory and Calculationsmentioning
confidence: 99%
See 1 more Smart Citation